Psychology Statistics Course Based Completely on Open Source Materials and Statistical Analysis Applications - Bernhardt, Paul (My University, 2021)
Package is a course cartridge from Canvas of a course on statistics for psychology students using only open-source materials. The course includes two forms for each of 3 exams, 3 student projects, and 8 chapter homework assignments. The main textbook is a fork of a book using examples from R. The main statistical software package referenced in the materials is a fork of R. The main open-source materials are Navarro & Foxcraft’s Learning Statistics with jamovi: A tutorial for Psychology Students and Other Beginners (version 0.70; DOI: 10.24384/hgc3-7p15 from http://learnstatswithjamovi.com) and the statistical analysis software application, jamovi (www.jamovi.org). All materials in this course cartridge are offered CC: BY-SA. (jamovi is not included, downloadable by all users)
Keywords: Psychology, Statistics; open education, open education resources